THE POTENTIAL ACTIVITY OF ASIATICOSIDE FROM AKAR MANIS (Glycyrrhiza glabra) AS HYPOLIPEMIC - Prasetyawan, Fendy; Saristiana, Yuneka; Salmasfattah, Novyananda; Mildawati, Ratna; Mayasari, Shinta (Transpublika Publisher, 2024)
Asiaticoside, a bioactive compound derived from Glycyrrhiza glabra (licorice root), has garnered attention for its potential as a hypolipemic agent. This study explores the lipid-lowering effects of asiaticoside, focusing on its mechanism of action and pharmacological properties. In silico analysis showed a high activation probability (pa=0.934) for asiaticoside, indicating its strong potential to interact with targets involved in lipid metabolism, such as PPAR-α, and reduce blood lipid levels. Additionally, its low inhibition probability (pi=0.003) suggests minimal risk for non-specific biological interference, making it a promising candidate for therapeutic use with a favorable safety profile. Asiaticoside’s antioxidant and anti-inflammatory properties further enhance its potential for cardiovascular protection by reducing oxidative stress, a key factor in atherosclerosis. While preliminary in silico results are promising, further in vitro and in vivo studies are required to confirm its efficacy, safety, and pharmacokinetics. Overall, asiaticoside represents a promising natural agent for managing hyperlipidemia and related metabolic disorders, offering an alternative to conventional synthetic therapies.